8 TH GRADE STUDENTS' ATTITUDES TOWARDS MATHEMATICS APPLIED GUIDANCE ACTIVITIES AND MATHEMATICS COURSE SUCCESS APPLIED GUIDANCE ACTIVITIES - Minisker, Melis; Ucecam, Kenan (JOURNAL OF ADVANCES IN MATHEMATICS, 2015)
The purpose of this study is to research the act of students' attitudes towards mathematics and mathematics course success to applying 8th grade students of guidance activities.This research is designed as pretest / posttest experiment and control group quasi-experimental design model. The research sample is consisted of two class that total of 40 students studying in 8th branch, at 2012 - 2013 academic year in a special primary school classroom in the district of Hatay Dortyol. The experimental group is consisted of first half of these students and the control group is consisted of the other half. Total of 12 guidance activities program has been implemented to experimental group twice a week for 6 weeks. Each activity is applied at the end of the courses for 60 minutes. There has not been any action applied to control group during this time.The mathematics achievement test (MAT) and scale of attitudes towards mathematics (SATM) is applied to all groups as the data collection tool in research. Analysis of all the data obtained from tests which are applied to students, are made by using the package programe SPSS-17. This data belongs to the mean, standard deviation, frequency and percentage values analyzed with descriptive statistics. Independent groups t test is used for solving the the research problems. At the end of the research; a significant difference about mathematics success are found in favor of the experimental group students, between 8th branch students who participated in the experimental group guidance activities and the students who did not receive guidance activities in the control group.At the same time; a significant difference about attitudes towards mathematics are found in favor of the experimental group students, between 8th branch students who participated in the experimental group guidance activities and the students who did not receive guidance activities in the control group.